The eleventh day : the full story of 9/11 and Osama bin Laden - Summers, Anthony; Swan, Robbyn (New York : Ballantine Books, 2011)
Draws on thousands of recently released official documents and new interviews to present a report on the September 11 attacks that examines why the crisis was not prevented, how the government and military responded, and who was behind it.
Includes bibliographical references (p. [569]-577) and index.
Keywords: September 11 Terrorist Attacks, 2001.; Terrorism -- United States -- Case studies; September 11 Terrorist Attacks, 2001.; Terrorism -- United States -- Case studies